2015 IEEE International Conference on Mechatronics (ICM) 2015
DOI: 10.1109/icmech.2015.7084045
|View full text |Cite
|
Sign up to set email alerts
|

Common zeros in synchronization of high-precision stage systems

Abstract: In synchronization of high-precision motion systems, in particular the synchronization between a wafer stage system and a reticle stage system of a wafer scanner, a novel feedforward structure is studied. In this structure, the numerator of each plant model is described by an input shaping filter capturing the zeros of said model. The denominator is described by a feedforward filter capturing the poles. Ideally, this gives zero error tracking of both the reticle and wafer stage systems without the need for pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Several studies contribute to enhance the lithography process. Some of these contributions are focused on the control aspect of the machine, as in [1,[9][10][11][12][13], and others are focused on introducing novel devices (or mechanisms) to improve the performance of this machine, as in [14][15][16].…”
Section: Existing Literaturementioning
confidence: 99%
“…Several studies contribute to enhance the lithography process. Some of these contributions are focused on the control aspect of the machine, as in [1,[9][10][11][12][13], and others are focused on introducing novel devices (or mechanisms) to improve the performance of this machine, as in [14][15][16].…”
Section: Existing Literaturementioning
confidence: 99%
“…The potential and industrial acceptance of add-on controller extensions has been confirmed in several preliminary ad hoc experimental studies. Research examples of improved synchronization by advanced feedforward can be found in Navarrete, Heertjes, and Schmidt (2015), see also Boeren, Bruijnen, van Dijk, and Oomen (2014) for related feedforward results. In Barton and Alleyne (2007) and Mishra, Yeh, and Tomizuka (2008) improved synchronization is achieved by using iterative learning control.…”
Section: Introductionmentioning
confidence: 99%
“…The present paper extends this to a more general setting containing more detailed proofs and explanation, and, in addition, C3, C4. Research related to results presented here includes Barton and Alleyne (2007), Temizer (2012), Lambregts, Heertjes, andvan der Veek (2015), Navarrete et al (2015) and Sakata and Fujimoto (2009). The framework guarantees robust stability under uncertainty in the system dynamics, finite accuracy of the plant model and neglected subsystem interaction components.…”
Section: Introductionmentioning
confidence: 99%